Prinsip Palemahan Sebagai Kontrol Pelestarian Lingkungan Hidup Dalam Hukum Hindu - Nyoman Widyani; I Nengah Juliawan (PARIKSA: Jurnal Hukum Agama Hindu, 2021)
Human beings have a great responsibility and influence on environmental changes around it and environmental management including prevention, damage and pollution management and environmental quality recovery has demanded the development of various policy tools and programs and activities supported by other environmental management support systems. Hindu law is a Dharma derived from Rta. Religion itself is also a moral norm or rule that is directly derived from the revelation of God Almighty. Tri Hita Karana in general shows the existence of recognized philosophical, sociological and ecological values and characterizes the integration and balancing of 3 (three) elements of life: God, nature and man. The concept of Palemahan as the principle of community life becomes an integral part of the awig-awig of Pakraman Village. Palemahan as a control of environmental preservation in Hindu law and its relevance to environmental conservation efforts as an effort to control the pattern of people's lives. Normative legal research using literature studies is legal research that places the law as a building system of norms. Descriptive-analytical research specifications. Data collection methods used through library research methods and data are analyzed qualitatively-normatively.